Analisis Kualitas Informasi Akuntansi Diukur Dengan Kualitas Akrual Sebelum Dan Selama Pandemi Covid-19 - Falen Sopia S. Aronggear; Sylvia Christina Daat; Pascalina V. S. Sesa (JURNAL AKUNTANSI DAN KEUANGAN DAERAH, 2023)
This study aims to empirically determine the difference in the quality of accounting information as measured by the quality of accruals before and during the COVID-19 pandemic in manufacturing companies listed on the Indonesia Stock Exchange. The 2018-2021 observation period. Â This study used a quantitative approach with secondary data. Sample selection using the purposive sampling method so that the samples used are 53 samples. With the population of manufacturing companies listed on the Indonesia Stock Exchange (IDX) Observation period 2018-2021. The analysis method used is multiple regression with the help of IBM 21 SPSS software with analysis techniques, namely documentation. The results showed that the quality of accounting information before and during the COVID-19 pandemic, as measured by the quality of accruals, was a significant difference. For example, the practical value before the pandemic was 78,607.85. Meanwhile, the considerable importance during the COVID-19 pandemic was 189.59. This means there is a substantial difference in the quality of accounting information as measured by the accruals quality. Thus, it can be stated that the COVID-19 pandemic in Indonesia can significantly affect the quality of accounting information as measured by accrual quality.